A New Approach Of Dewatering Fine Mass Products - W. H. Stahl (Society for Mining, Metallurgy & Exploration, 1983)
The continuous vacuum filtration is the solid-liquid separation process that is nowadays most frequently used in the beneficiation industry all over the world. After a development time of several decades, the various filter types such as drum filter, disk filter, plate filter and belt filter can be consideres as a sound functional design ensuring a trouble-free operation. Nevertheless, the vacuum filtration does no longer meet the present and future technological requirements. The moisture content of filter cakes is too high. Their thermal secondary drying is too expensive (coal, ores) and may bring about undesirable material changes and the filter cake conditioning with water-binding substances for dumping purposes is too costly.